Gaya Hidup Konsumtif Gen Z dan Implikasinya terhadap Perencanaan Keuangan: Sebuah Kajian Literatur - Christine Monica Saren; Titik Suhartini (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Generation Z is known as a group that grew up in the era of digitalization with wide access to information and financial technology.Lifestyle changes marked by digital-based consumption, social media trends, and a preference for experiences over ownership have significantly impacted their financial behavior.This research aims to analyze how the consumerist lifestyle of Gen Z affects their financial planning patterns, including saving habits, debt management, and investment decisions.Through a literature review of various previous studies, this research identifies the main factors driving Gen Z's consumption patterns and how financial literacy levels play a role in shaping their financial behavior.Additionally, this research explores the challenges faced in financial planning due to a consumerist lifestyle, such as the tendency for impulsive purchases, high usage of digital credit services, and lack of long-term financial planning. The findings of this study are expected to provide insights for academics, financial practitioners, and policymakers in designing more effective financial education strategies for the younger generation.The conclusion of this study highlights the importance of financial literacy in helping Gen Z manage their finances more wisely amidst the increasingly prevalent consumer lifestyle.